1984
DOI: 10.1073/pnas.81.23.7608
|View full text |Cite
|
Sign up to set email alerts
|

The neurula stage mouse embryo in control of neuroblastoma.

Abstract: The purpose of this study was to determine whether the neurula stage mouse embryo can regulate tumor formation of C-1300-3 neuroblastoma cells. Five neuroblastoma cells were injected into the second somite of neurula stage embryos, and their ability to form tumors was tested, 24 hr later, by transplanting the portion of the embryo containing the cancer cells into the testes of adult mice. Only one-third the number of tumors was obtained in comparison with controls in which (i) five neuroblastoma cells were inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 26 publications
(20 reference statements)
2
31
0
Order By: Relevance
“…In addition, studies have documented the participation of teratocarcinoma cells in normal mouse development after their transplantation into the blastocyst (21)(22)(23)(24)(25)(26) and regulation of differentiation of other tumor cell types by appropriate embryonic fields (27,28). These studies suggested that the phenotype expressed by transformed cells is dynamic and subject to normalization in response to epigenetic (microenvironmental) regulation (26).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have documented the participation of teratocarcinoma cells in normal mouse development after their transplantation into the blastocyst (21)(22)(23)(24)(25)(26) and regulation of differentiation of other tumor cell types by appropriate embryonic fields (27,28). These studies suggested that the phenotype expressed by transformed cells is dynamic and subject to normalization in response to epigenetic (microenvironmental) regulation (26).…”
Section: Discussionmentioning
confidence: 99%
“…Some success with in vitro culture of 8-to 10-day embryos has been obtained in tissue culture (10,14,15), but later events in development have been studied, usually in organ culture (16) or with avian embryos (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…The morphogenetic field ought to be the most active and accessible during embryogenesis. It is thus not surprising that despite considerable malignancy and aneuploidy, tumor cells introduced into wild-type embryos become integrated (figure 1(C)) as normal tissue [124][125][126][127][128][129][130][131][132][133][134]. Human metastatic melanoma cells injected into zebrafish embryos acquire a non-neoplastic phenotype, but form tumors when injected into zebrafish after organogenesis [135,136].…”
Section: Cancer As a Disease Of Anatomical Homeostasismentioning
confidence: 99%